2017
DOI: 10.1080/23279095.2017.1326047
|View full text |Cite
|
Sign up to set email alerts
|

Semantic verbal fluency impairment is detectable in patients with subjective cognitive decline

Abstract: Patients with subjective cognitive decline (SCD) are at higher risk for conversion to dementia due to Alzheimer's disease (AD). Semantic verbal fluency (SVF) seems to be impaired in the early stages of AD. The goal of the present study was to identify the discriminative potential of verbal fluency (VF) in patients with SCD to show if very early signs of cognitive decline may be detected in SCD. We examined 93 normal controls (NC) and 61 participants with SCD. Each participant was administered a comprehensive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 55 publications
5
17
0
2
Order By: Relevance
“…Additionally, to delineate the neural regions associated with the level of performance on the verb fluency task, linear regression analysis was used with the total number of correct verb produced as a covariate of interest across all 16 participants using the [verb fluency > rest] contrast images. As dementia progresses, decreased performance on verbal fluency tasks is observed, and verbal fluency deficits are known pathological markers of cognitive declines due to dementing diseases, even though the deficits are also observed in subclinical populations (Clark et al, 2009;see Belleville et al, 2017;Nikolai et al, 2018). Furthermore, structural and functional neuroimaging studies related to verbal fluency tasks in individuals with MCI or dementia have suggested that cognitively healthy older adults and individuals with dementia exhibit similar brain activation patterns or structural brain changes, differing only in terms of level of activation (i.e., decreased activation in AD; Arai et al, 2006;Metzger et al, 2016) or severity of structural or perfusion changes (Östberg et al, 2007;Metzger et al, 2016;Rodríguez-Aranda et al, 2016).…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, to delineate the neural regions associated with the level of performance on the verb fluency task, linear regression analysis was used with the total number of correct verb produced as a covariate of interest across all 16 participants using the [verb fluency > rest] contrast images. As dementia progresses, decreased performance on verbal fluency tasks is observed, and verbal fluency deficits are known pathological markers of cognitive declines due to dementing diseases, even though the deficits are also observed in subclinical populations (Clark et al, 2009;see Belleville et al, 2017;Nikolai et al, 2018). Furthermore, structural and functional neuroimaging studies related to verbal fluency tasks in individuals with MCI or dementia have suggested that cognitively healthy older adults and individuals with dementia exhibit similar brain activation patterns or structural brain changes, differing only in terms of level of activation (i.e., decreased activation in AD; Arai et al, 2006;Metzger et al, 2016) or severity of structural or perfusion changes (Östberg et al, 2007;Metzger et al, 2016;Rodríguez-Aranda et al, 2016).…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…Thus, various brain areas responsible for these cognitive processes would need to be actively recruited when a person performs a verbal fluency task, and our current finding of a contribution from the hippocampus as a "nonlanguage" structure (Glikmann-Johnston et al, 2015) is not unexpected. For example, medial temporal lobe (MTL) and adjacent areas have been reported to be integral to semantic networks, and activations in these regions have been found to be significantly associated with semantic fluency performance given their role in extracting information from semantic storage (Pihlajamäki et al, 2000;Glikmann-Johnston et al, 2015;Kochhann et al, 2018;Nikolai et al, 2018). In the current study, the upregulation of MTL and related regions in those who showed poorer verb fluency performance may have been due to the concurrent recruitment of brain areas responsible for language and cognitive abilities (Li et al, 2017), which are important for fluency.…”
Section: The Involvement Of Subcortical Structures and Medial Temporamentioning
confidence: 99%
“…Nikolai et al . noted that patients with SCD presented with impairment in category verbal fluency compared with healthy controls . Koppara et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nikolai et al noted that patients with SCD presented with impairment in category verbal fluency compared with healthy controls. 32 Koppara et al reported that functional decline in the immediate and delayed memory and verbal fluency occurred prior to the onset of SCD. 33 Further, a previous study reported that category verbal fluency was associated with temporal region.…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of the present study was to assess the R4Alz battery's ability to differentiate SCD from cognitively healthy adulthood (young to older adults) and MCI. Even though a few studies indicate that some cognitive deficits such as in semantic verbal fluency are detectable in people with SCD [48], to our knowledge, no specific cutoff scores for differentiating SCD from cognitively CHA exist till now. On the contrary, the criteria for the diagnosis are based on the criteria of the SCD-I Working Group and on specific self-administered memory complaint questionnaires that are usually used [46,49,50].…”
Section: R4alz Differential Abilitymentioning
confidence: 95%